A Meta-Analysis: The Relationship Between Parental Involvement and Latino Student Outcomes. (January 2017) - Jeynes, William H.
This meta-analysis of 28 studies examines the relationship between parental involvement and the academic achievement and school behavior of Latino pre-kindergarten-college-age children. Analyses determined the effect sizes for parental involvement overall and specific categories of involvement. Results indicate a significant relationship between parental involvement and academic achievement and overall outcomes, but not for school behavior. This relationship between involvement and academics existed both for younger (grades K-5) and older (secondary school and college freshman) students, as well as for certain specific components of parental involvement. Parental involvement, as a whole, was associated with better school outcomes by .52 of a standard deviation unit. The significance of these results is discussed.